2017
DOI: 10.1148/radiol.2017162857
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Retention in the Rat Brain: Assessment of the Amounts of Insoluble Gadolinium-containing Species and Intact Gadolinium Complexes after Repeated Administration of Gadolinium-based Contrast Agents

Abstract: Purpose To evaluate the speciation of gadolinium-containing species after multiple administrations of the gadolinium-based contrast agents (GBCAs) gadodiamide and gadoteridol and to quantify the amount of intact gadolinium complexes and insoluble gadolinium-containing species. Materials and Methods A total dose of 13.2 mmol per kilogram of body weight of each GBCA was administered in healthy Wistar rats over a period of 8 weeks. Three days after the final administration, rats were sacrificed, and the brains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
135
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 32 publications
11
135
1
Order By: Relevance
“…However, mechanism and chemical form of Gd retention in the body still need to be defined. More recently, it has been shown that the repeated use of GBCA could lead to the Gd deposition in various organs including brain, kidney, bones, and so forth (Do et al, ; Gianolio et al, ; Kanda et al, ; Reeder & Gulani, ; Runge, ). Because of these growing concerns and potential toxicity of GBCAs, the European Medicines Agency (EMA) has suspended or restricted the use of linear GBCAs in Europe.…”
Section: Gadolinium‐based Contrast Agentsmentioning
confidence: 99%
“…However, mechanism and chemical form of Gd retention in the body still need to be defined. More recently, it has been shown that the repeated use of GBCA could lead to the Gd deposition in various organs including brain, kidney, bones, and so forth (Do et al, ; Gianolio et al, ; Kanda et al, ; Reeder & Gulani, ; Runge, ). Because of these growing concerns and potential toxicity of GBCAs, the European Medicines Agency (EMA) has suspended or restricted the use of linear GBCAs in Europe.…”
Section: Gadolinium‐based Contrast Agentsmentioning
confidence: 99%
“…To tackle this task, we evaluated the speciation of gadolinium containing species in rats' brains after multiple administrations of Gd(DTPA‐BMA) and Gd(HP‐DO3A) . This work allowed us to quantify the amount of intact gadolinium complexes and to evaluate the occurrence of insoluble gadolinium containing species.…”
Section: What Do We Know About the Chemical Form Of The Retained Gmentioning
confidence: 99%
“…Summary of the experimental protocol used to assess total gadolinium, the amount of intact GBCA, and Gd in insoluble forms. Adapted from ref . Copyright 2017 Radiological Society of North America.…”
Section: What Do We Know About the Chemical Form Of The Retained Gmentioning
confidence: 99%
“…Studies using animal models have shown that GBCAs may be deposited in the brain after repeated injections [1][2][3]. Tissue depositions of linear GBCAs are much higher than those of macrocyclic GBCA.…”
mentioning
confidence: 99%
“…Furthermore, the Gd deposition has also been observed in the cerebellar cortex [3,7]. Gd compounds deposited in the cerebellum consist of both soluble and insoluble forms [1,2]. Soluble form may be intact GBCA, whereas insoluble form may be Gd bound with organic or inorganic anions, although the exact chemical nature of insoluble form has not yet fully clarified.…”
mentioning
confidence: 99%